Health Seeking Behavioural Pattern Among Patients Of Neuro-Psychiatric Hospitals In Akure: Implication For Health Promotion Education - Olorunsogo, R. T.; Adebola, O. G.; Alofun, G. O. (Journal of Science, Technology and Innovation Research, 2025)
This study validated the enormity of mental illness as a challenge that is prevalent among people of all ages in Nigeria, regardless of other demographic factors including education, gender, wealth index, marital status among others. A more challenging situation is the negligence of seeking treatment and the prevalence of seeking help from only spiritual places. This shows that there is dire need for enlightenment and health promotion programs. Consequently, the study recommends, intense attention for quality reorientation for a cultural shift in the way mental illness is perceived, so that correct avenues will be sought for treatment; it also encourages the government to pay more attention to providing more facilities for such treatment to be accessible to all. Health insurance scheme can be used to cover for the cost of treatment under the universal health coverage system among others.